STEROL METHYLTRANSFERASE 1 Controls the Level of Cholesterol in Plants - Diener, Andrew C. (American Society of Plant Physiologists, 2000)
The side chain in plant sterols can have either a methyl or ethyl addition at carbon 24 that is absent in cholesterol. The ethyl addition is the product of two sequential methyl additions. Arabidopsis contains three genes—sterol methyltransferase 1 (SMT1), SMT2, and SMT3—homologous to yeast ERG6, which is known to encode an S-adenosylmethionine–dependent C-24 SMT that catalyzes a single methyl addition. The SMT1 polypeptide is the most similar of these Arabidopsis homologs to yeast Erg6p. Moreover, expression of Arabidopsis SMT1 in erg6 restores SMT activity to the yeast mutant. The smt1 plants have pleiotropic defects: poor growth and fertility, sensitivity of the root to calcium, and a loss of proper embryo morphogenesis. smt1 has an altered sterol content: it accumulates cholesterol and has less C-24 alkylated sterols content. Escherichia coli extracts, obtained from a strain expressing the Arabidopsis SMT1 protein, can perform both the methyl and ethyl additions to appropriate sterol substrates, although with different kinetics. The fact that smt1 null mutants still produce alkylated sterols and that SMT1 can catalyze both alkylation steps shows that there is considerable overlap in the substrate specificity of enzymes in sterol biosynthesis. The availability of the SMT1 gene and mutant should permit the manipulation of phytosterol composition, which will help elucidate the role of sterols in animal nutrition.